DEVELOPMENT OF FUNCTIONAL AUDITOR COMPETENCY MODEL IN INSPECTORATE INSTITUTION - Rosarianto Mariano Amleni (Yogyakarta State University, 2020)
This study aims to review and develop auditor inspectorate competency model in Timor Tengah Utara (TTU) regency to support the implementation of supervisory duties. This study uses a qualitative-descriptive method with data collection techniques through observation and interview. Data analysis method used in this research is literature study. The results of this study found problems related to work discipline and auditor's personal safety. The development of competencies safety awareness requires auditors to be able to identify and improve situations that have an impact on personal safety in each process of carrying out supervision whereas the development of competencies time management requires auditors to be able to plan and regulate the use of time in setting priorities in carrying out supervisory duties with the result that they can be carried out effectively.